The Difference THE DIFFERENCE OF FATIGUE LEVEL AMONG MORNING, AFTERNOON AND NIGHT SHIFT WORK ON WORKER OF STEVEDORING IN TENAU KUPANG PORT - OLGA MARIANA DUKABAIN (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2013)
Fatigue is a common occur on labor. All types of work will result in fatigue of working. Fatigue while working will degrade performance and increase the error rate of work. Increasing of the error in work will provide possibility of work accident in an industry that may impact on workers' disability even the most fatal is death. Factor of shift work, workload, physical environment such as temperature, humidity, lighting and noise can lead to fatigue in workers. This study aimed to find out the fatigue rate differentials shift work in morning, afternoon, and evening on Labor of Stevedoring in Tenau Kupang Port. This type of research was survey observational with Cross sectional approach, and the number of samples is 89 respondents consisting of 37 people in the morning shift, 24 people in the aternoon shift and 28 people in night shift. Sample were taken with purposive sampling. Collection data were done by interviewing respondent, measuring factors of physical environment (temperature, humidity), measurement of workload before and after work. Then research data were analyzed univariat and bivariat with statistical tests product moment correlation and test the difference by using one way anova and kruskal-wallis. The results of this studi an average level of fatigue after working was 450,91 ms (medium), in the morning shift consisting of 468,04 ms (medium), the afternoon shift consisting of 449,47 ms (medium). Analysis result of workload, temperature, humidity is known that workload have a significant relationship with fatigue by analysis product moment (P=0,001,CI=95 %). The test results one way anova obtained that there is significant differences in temperature, humidity, between work shift in morning, noon and night (P=0,000), there is significant differences in level of fatigue before and after work (P=0,001), there is significant differences in fatigue between work shift in morning, noon and night (P=0,013). Concluded that there is a meaningful relation between work load with fatigue, temperatue and humidity with fatigue and there are difference in levels of fatigue between work shift in morning, noon and night in Tenau Kupang Port.